Optimalisasi Sistem Destinasi Wisata (SIDETA) Di Dinas Pariwisata Kota Padang - Syifana Azra; Syamsir Syamsir; Rifaldi Makriwal; Viska Anggraini; Ulfa Durrota Aini Fedrya; Rani Handriyani (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
This research was motivated by the launch of the Tourist Destination System (SIDETA) application by the Padang City Tourism Office in 2021 as an effort to increase the number of visits by local and foreign tourists in Padang City. This research was conducted with the aim of describing the implementation and optimization of the SIDETA application at the Padang City Tourism Office. This type of research is descriptive qualitative. Data was collected through field studies using interview, observation and documentation techniques. The results of this research describe that overall SIDETA is still in the development and optimization stage in its application as an information system in government agencies. Based on the stages of E-Government implementation proposed by ASPA (American Society for Public Administration), SIDETA implementation is at the interactive stage. Furthermore, in 2023, through collaboration with the Padang City Communications and Information Service, the SIDETA application was transformed into a website that can be accessed via the page https://pariwisata.padang.go.id/ which contains home features, city profile features, service features, destination features tourism, event features, culinary and shopping features, features about fields, publication features and video features. Based on the E-Governance theory according to Djoko Agung Harijadi, there are 6 obstacles in implementing SIDETA in the Padang City Tourism Office, namely communications infrastructure, funds, human resources, culture, regulations and leadership. The efforts to optimize the implementation of SIDETA are carried out by the Padang City Tourism Office, namely socialization related to SIDETA which is handed over to tourism awareness groups directly under the auspices of the Padang City Tourism Office so that they become agents who socialize and promote SIDETA to the wider community in addition to promoting tourism in their own area.